Metaphor in Bulgarian and Russian economic terminology: types of metaphorical models (based on terminological phraseological units) - Стоянова, Радостина (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The study focuses on the process of metaphorization in contemporary Bulgarian and Russian terminology in economics, as seen in terminological phraseologisms. A number of basic metaphorical models in this domain are identified: anthropomorphic, sociomorphic, artefactual, and naturomorphic. A rolling sample of terminological phraseologisms has been analyzed, allowing the identification of the most productive conceptual domains that are the sources of metaphors for economic terminology.